Queer Archives, Queer Content, Queer Movement : A comparative Study of Governing Documents of Queer (and) Leather Community Archives - Procopé,Vendela (2025)
This thesis examines queer community archives (QCAs) and their governing documents in order to gain a better understanding of how they define themselves, their work, and the communities they serve. Focusing on archives associated with queer, leather, BDSM, and fetish communities, specifically The Queer Movement Archives and Library (QRAB) and the Leather Archives & Museum (LA&M), it examines the way statements of purpose, visions, statutes, collection policies, and texts about the archive reflect both archival practice and community belonging. By analysing and comparing their governing documents through the lens of queer archival theory and theories of sexuality, desire, and community, the research shows how these archives operate as spaces of memory, meaning-making, and social intervention. Governing documents are both performative and practical and guide archival work by situating the archive within its social and cultural context, as well as reflecting the expressed needs of the communities they serve. Drawing on José Muñoz’s concept of queer worldmaking (2009), the research shows how these archives foreground histories that have often been marginalised, disregarded, or defined by others. Community archives not only safeguard memory in the face of marginalisation but actively create social and communal spaces that foster care, solidarity, and collective identity. With a focus on the practical and affective aspects of governing documents, the thesis provides a critical examination of how QCAs negotiate power, belonging, and desire, to promote community-driven archival practices that counter normative frameworks of sexuality, gender, and community. The research contributes to archival studies by showing how community archives navigate memory, identity, and desire, emphasising the role of governing documents play in shaping both the practical and imaginative efforts of queer archival work.
Keywords: arkivvetenskap